PRIVATISASI BADAN USAHA MILIK NEGARA (BUMN) DI INDONESIA - Rorong, Ita Pingkan (Journal of Indonesian Applied Economics, 2008)
This article  is made  in order  to  find a model of BUMN privatization  that able  toprovide benefits  for  the government and  the  Indonesian people  in the  future, andalso able to improve the performance of the BUMN themselves, so that they can beexist  and  could  compete  in  the  world market.  This  paper  concludes  that  theprivatization of BUMN to the private placement method by foreign investors with theinvestment in above 50% will provide the most optimal benefits. Some benefits willbe obtained by using this model of privatization, including the increase of the abilityto  access  opportunities  in  the  international  market,  the  existence  of  technologytransfer, the occurrence of positive changes in work culture, and the application ofprinciples of good corporate governance in the management of BUMN. In order tominimize the risk of rejection in the privatization process of BUMN, it is suggestedthat the government should make a clear privatization of state-owned systems andprocedures, adequate dissemination to relevant parties, as well as implementing atransparent privatization process.Keywords: privatization, BUMN, income’s distribution